Prefactibility study for the widespread installation of the SLACE system - Martinez, J.A; Gonzalez, J.M; Planas, J.R (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
The main objective of the SLACE system (automatic reading of electricity meters) is to obtain automatic readings from customer's watthour meters, but it also offers other additional uses. The system comprises a series of different units which are all interconnected in different ways. Its characteristics and functions are described in this paper. (6 pages)